Self - presentation attractiveness in social and intellectual sphere in threat to self situations among women and men of different self-esteem - Stojanowska, Elżbieta (Studia Psychologica: Theoria et praxis, 2011)
The purpose of experimental research was establishing the role of self-esteem and kind of threat for self-presentation attractiveness in social sphere and intellectual among women and men. Research carried out in group of 120 persons showed that self-esteem differentiated self-presentation attractiveness to different manner among women and men. In female group, independently on situation and declared effort to express definite features, low self-esteem subjects were more attractive in social sphere than high selfesteem persons, however, they did not differ in attractiveness of instrumental sphere. Then in group of man, independently on situation, high self-esteem persons were more attractive in instrumental sphere than low self-esteem persons, but in social sphere, in neutral situation equal as well as social threats, low-self-esteem people were estimated higher than high self-esteem people. Research have showed small sex differences in range of motivation and attractiveness of self-presentation.